Fostering Disaster Resilience through a Dual Strategy: Early Warning-Emergency Response Systems and Ecological Recovery - Hendrayanto (Media Konservasi, 2025)
The recurrent incidence of floods and flash floods across various regions of Indonesia has incited ongoing public and scholarly discourse that attributes hydrometeorological factors and deforestation as principal contributors to hydrometeorological disasters. This perspective adds a view angle to typical cause-and-effect discussions about floods and flash floods, proposing a two-pronged approach to address their challenges. Though not entirely new, it emphasizes the importance of prioritizing disaster prevention over simply managing the aftermath.